Effectiveness of Counting Tree Media in Enhancing First-Grade Students’ Addition Skills at Madrasah Ibtidaiyah - Syafa'atul Laili; Ulfatus Sofiana; Yuniyah Fatmawati; Ria Resti Fauziah; Rahmat Rudianto (Information Technology and Science (ITScience), 2026)
Mathematics learning in the lower class of Madrasah Ibtidaiyah requires the use of real media so that students can understand the concept of abstract calculation operations, especially in the material of summing numbers 1 to 10. A lack of understanding of concepts and student learning outcomes shows the need for innovation in learning media that is in accordance with student development. One of the concrete media that can be used is the Counting Tree media. This medium allows students to learn by manipulating objects directly. This study aims to determine the effectiveness of the Counting Tree media in improving the ability of summation counting operations of grade I students of MI Al-Azhar Menganti Gresik. This study uses a Classroom Action Research (PTK) design with a mix-methods approach. The research subjects consisted of 25 students in grade I. The research was carried out in two cycles which included the stages of planning, implementation of actions, observation, and reflection. Data collection techniques include observation of teacher and student activities, learning outcome tests, and student response questionnaires. The results of the study showed an increase in teacher and student activity with the category of very good. The completeness of student learning outcomes increased from 64% in the first cycle to 94% in the second cycle. The reason is that the Counting Tree media is effective in improving the ability of addition calculation operations and creating more meaningful mathematics learning for low-grade students.